Antifungal and antibacterial effect of dodder (Cuscuta campestris) used for hepatitis treatment of mothers and newborn infants in Province Mardin in Turkey - Erecevit Sönmez, Pınar; Kirbağ, Sevda; İnci, Şule (Centenary University, 2019)
Dodder is a plant used for the hepatitis treatment in new born infants in and around Mardin. The aim of this research to determine the antifungal and antibacterial effects of traditionally used dooder is known as a regional folk remedy. Thus and so, the efficacy of the drug has been demonstrated by the inclusion of natural therapeutic antimicrobial agents such as anti-inflammatory and wound healing, including infectious diseases. The antimicrobial effects of these plant was analyzed against bacteria, yeast and dermatopyta fungi by the agar disc diffusion method. The nominal concentration of the plant to prevent from the development of microorganisms was detected with the broth microdulitions method. It was determined that it had sensitive and moderately sensitive antimicrobial effect against all of microrganisms (13-19.66 mm/inhibition zone), growth of tested microrganisms were inhibited at 50-6.25 µL.It is though that this natural herbal resource can light the way for treatment of several diseases and direct the next studies because of having the potential for being used as a new antimicrobial agent. © 2019, Centenary University. All rights reserved.
Türkiye'de Mardin ilindeki annelerin ve yenidoğan bebeklerin sarılık tedavisinde kullanılan küsküt'ün (Cuscuta campestris) antifungal ve antibakteriyel etkileri
Keywords: Agar disc diffusion method; Antimicrobial effect; Dodder; Pathogen microorganisms; The broth microdilution